2020
DOI: 10.1016/j.pmedr.2020.101273
|View full text |Cite
|
Sign up to set email alerts
|

Associations between living alone, depression, and falls among community-dwelling older adults in the US

Abstract: Social isolation is closely linked to depression and falls in late life and are common among seniors. Although the literature has highlighted age-related variations in these three geriatric conditions, evidence on heterogeneities across older adult age categories is lacking. To address this gap, we present cross-sectional analyses using indicators of social isolation, depression, and falls of older adults constructed from the most recent Behavioral Risk Factor Surveillance System (BRFSS) data. An age-based und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…In this research, by the previous literature, living alone positively relates to depression (Das Gupta et al, 2020;Djernes, 2006;Gyasi et al, 2020;Hu et al, 2012;D. Russell & Taylor, 2009;Stahl et al, 2017).…”
Section: Discussionsupporting
confidence: 55%
“…In this research, by the previous literature, living alone positively relates to depression (Das Gupta et al, 2020;Djernes, 2006;Gyasi et al, 2020;Hu et al, 2012;D. Russell & Taylor, 2009;Stahl et al, 2017).…”
Section: Discussionsupporting
confidence: 55%
“…Although prior evidence is less than clear on which characteristics of places are supportive of aging (NAS, 2018), lower social environment and support in cities has often been identified as a limiting factor (Hofferth & Iceland, 1998; White & Guest, 2003). Social connection and support of seniors, especially support for the oldest-old living alone (Das Gupta et al, 2020), may be of greater concern in age-segregated communities in urban areas. Prioritizing resources for innovative local and area programs addressing isolation of seniors is therefore imperative given the evidence of a positive association between quality of governmental services and health and wellbeing of older adults in general (Hogan et al, 2016) and during the current pandemic, in particular (Hoffman et al, 2020; Pendergrast, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…12 This multisensory stimulation processing could be diminished in older adults, due to a lack of new sensory experiences or enriched environments, caused by social isolation and the decrease in physical interaction. 13 This could be a prime factor of change, since some authors have shown that sensory stimulation, specifically time-space, would be related to a healthy brain, reducing the probability of neurodegenerative disorders that are associated with dementia and other mental health disorders in aging. 14 In addition, the use of multisensory stimuli with great variability, such as exposure to new environments, including vestibular changes such as a simulated free fall or risk associated simulations like vertigo sensations, represent not only in an enriched environment and an increase of stimuli variability, but also the possibility of adaptation to new experiences.…”
Section: Introductionmentioning
confidence: 99%